Efek Car, Inefisiensi Biaya, Ldr Dan Ukuran Bank Terhadap Npl Bank Umum - Teguh Sutrisno, Mulkan (Graha Akuntansi, 2022)
The objective of the study is to examine the effect of Capital Adequacy Ratio (CAR),Cost Inefficiency (INEF),LDR and Bank Size (SIZE) on NPL in commercial banks. This research was conducted using secondary data. Population in this research was a commercial bank in OJK from 2011 up to 2013. Sampling technique used was purposive sampling. There are 56 commercial banks being analysed. This study uses regression analysis. The research proves that the CAR have negative and not significant impact on NPL,Cost Inefficiency (INEF), LDR and Bank Size (SIZE) have positive and significant effect on NPL. Adjusted R Square is 0,141 this means thant 14.1% of the dependent variable can be explained by the independent variable , while the remaining 85.9 % is explained by other causes outside the model